Fourth Molars in the Anthropoidea - Daris R. Swindler (Dental Anthropology Association, 2002)
Fourth molars are not common in the anthropoidea. Orangutans possess the highest frequencies (7-13%) while many genera in the suborder lack the fourth molars. A review of the incidence of M4's in the Anthropoidea is presented and a description of the ontogeny of M4 in Macaca nemestrina is described and offered as an explanation of the development of M4's in this taxon.